Hepatocytes direct the formation of a pro-metastatic niche in the liver - Lee, Jae W.; Stone, Meredith L.; Porrett, Paige M.; Thomas, Stacy K.; Komar, Chad A.; Li, Joey H.; Delman, Devora; Graham, Kathleen; Gladney, Whitney L.; Hua, Xia; Black, Taylor A.; Chien, Austin L.; et al. (Nature (London), 2019)
The liver is the most common site of metastatic disease 1 . Although this metastatic tropism may reflect the mechanical trapping of circulating tumour cells, liver metastasis is also dependent, at least in part, on the formation of a ‘pro-metastatic’ niche that supports the spread of tumour cells to the liver 2 , 3 . The mechanisms that direct the formation of this niche are poorly understood. Here we show that hepatocytes coordinate myeloid cell accumulation and fibrosis within the liver and, in doing so, increase the susceptibility of the liver to metastatic seeding and outgrowth. During early pancreatic tumorigenesis in mice, hepatocytes show activation of signal transducer and activator of transcription 3 (STAT3) signalling and increased production of serum amyloid A1 and A2 (referred to collectively as SAA). Overexpression of SAA by hepatocytes also occurs in patients with pancreatic and colorectal cancers that have metastasized to the liver, and many patients with locally advanced and metastatic disease show increases in circulating SAA. Activation of STAT3 in hepatocytes and the subsequent production of SAA depend on the release of interleukin 6 (IL-6) into the circulation by non-malignant cells. Genetic ablation or blockade of components of IL-6–STAT3–SAA signalling prevents the establishment of a pro-metastatic niche and inhibits liver metastasis. Our data identify an intercellular network underpinned by hepatocytes that forms the basis of a pro-metastatic niche in the liver, and identify new therapeutic targets. Pancreatic cancer activates IL-6–STAT3 signalling in hepatocytes to induce the formation of a pro-metastatic niche in the liver.